Current and future perspectives of ethnomathematics as a program. ([2016]) - Rosa, Milton; D'Ambrósio, Ubiratan; Orey, Daniel Clark; Shirley, Lawrence; Alangui, Wilfredo V; Palhares, Pedro; Gavarrete, Maria Elena
No abstract available